Predicting current and future potential habitat distribution of fig tree (Ficus-Carica) in Morocco using Maxent Modeling - amal labaioui; Rachid Razouk; Lahcen HSSAINI (African and Mediterranean Agricultural Journal - Al Awamia)
Climate change scenarios predict that fruit tree production will be impacted mainly by drought and high temperatures. The fig tree is considered as a hardy tree resistant to drought which makes it, in the context of climate change, a good alternative to trees that consume too much water and are very demanding in terms of cold. This work was carried out with the objective of delimiting the areas suitable for the fig tree currently and by 2050 to guide the new plantations of the fig tree. To do this, we used current and future climate data from the Worldclim climate database and the Maxent model based on the maximum entropy principle to map the distribution area of the fig tree in Morocco. The results show that the environmental variables that most impact the distribution of the fig tree in Morocco are the precipitation of the coldest quarter (bio 19) the mean diurnal deviation (bio2) and the isothermality (bio3) and that fig tree area will decrease under the impact of climate change and will be limited to the North of Morocco mainly in the provinces of El Hoceima and Chefchaoun. Efforts to develop this sector must therefore focus on improving production techniques and choosing varieties that are better adapted to future climatic conditions.